Pengaruh Teknologi terhadap Perubahan Peranan Sektor Pertanian dalam Struktur Perekonomian Indonesia - Pantjar Simatupang; nFN Supriyati; Sudi Mardianto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1996)
The main objective of this study is to evaluate the pattern of Indonesia economic structural change and the roles of agricultural technology in affecting the pattern. The economic structure is measured with GDP and employment absorption shares composition by the economic sectors (agriculture, industry, and service). The direct impact of agricultural technology on the economic structure is evaluated with the supply side approach. The analysis is conducted with an econometric model using time series data of 1971-1991 period. The study shows that the pattern of Indonesian economic structural change is abnormal in the sense completely different from the experience of most developed countries. The economic structural change have been highly unbalanced, excessively burdened the agricultural sector with labor absorption. The study also shows that agricultural technology (measured with labor productivity) and real price are positively related with agricultural GDP share, but negatively related with the agricultural employment share. This explains why the directions of GDP shares is a contradictory with employment share. Accordingly the attempt to improve the pattern of economic structural change should be conducted with a multi sectoral policy package: increasing agricultural productivity and real price while increasing labor use intensity in the industrial sector.